Maitland Frederic William, Selected Historical Essays, chosen and introduced by Helen M. Cam - Adamus, Jan (Czasopismo Prawno-Historyczne, 1959)
Recenzja: Frederic William Maitland, Selected Historical Essays, chosen and introduced by Helen M. Cam, Cambridge, published in association with the Seiden Society at the University Press, 1957, s. XXXIX + 278.